2023
DOI: 10.1021/acsanm.3c02723
|View full text |Cite
|
Sign up to set email alerts
|

MXene Nanosheets Functionalized with Cu Atoms for Urea Adsorption in Aqueous Media

Zhihao Yen,
Teddy Salim,
Chris Boothroyd
et al.

Abstract: Ti3C2T x MXene is an emerging family of two-dimensional materials, and because of its large specific surface area, it has the potential for many applications. Herein, a new application using Cu-doped MILD (minimally intensive layer delamination)-synthesized Ti3C2T x MXene for urea removal is demonstrated. The doping of Cu on MXene results in an increase in its affinity for urea adsorption as compared to pristine MILD-synthesized MXene due to the formation of the Cu–urea complex. Previous computational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Ion exchange or surface functionalization of MXene can be used to remove the intercalated Li + ions, which in turn improves the urea adsorption energies for MXene. Functionalizing the surface with Cu significantly enhances the urea adsorption capability of this material, provided the Cu loading is sufficiently low so that Cu is evenly dispersed across the surface . This result was supported by DFT calculations, which showed that the formation of the Ti–O–Cu linkage increases the binding energy of urea to the surface .…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Ion exchange or surface functionalization of MXene can be used to remove the intercalated Li + ions, which in turn improves the urea adsorption energies for MXene. Functionalizing the surface with Cu significantly enhances the urea adsorption capability of this material, provided the Cu loading is sufficiently low so that Cu is evenly dispersed across the surface . This result was supported by DFT calculations, which showed that the formation of the Ti–O–Cu linkage increases the binding energy of urea to the surface .…”
Section: Introductionmentioning
confidence: 57%
“…Compared to the Glu MXene system, the Cu-functionalized Glu MXene (Cu 39.3 Glu MXene) exhibits additional paramagnetic influences from surface Cu 0 ions, particularly on the secondary and tertiary carbons, while the carboxylic acid remains relatively unaffected (Figure a,b). While Cu + is diamagnetic and should not contribute to paramagnetic influences in the NMR spectrum, our previous study revealed that Cu-functionalization results in Cu oxidation states between 0 and 1 . Cu 0 is paramagnetic and is thought to contribute to the paramagnetic broadening/shifting as well as the Ti 3+ ions.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations